2021
DOI: 10.1021/acs.jafc.1c06029
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Chito-oligosaccharides Improve Intestinal Immunity via Regulating Microbiota and Th17/Treg Balance-Related Immune Signaling in Piglets Challenged by Enterotoxigenic E. coli

Abstract: This study was conducted to investigate how chito-oligosaccharides (COSs) affect the growth performance and immune stress response and to further explain their mechanisms. A total of 32 boars that were 28 days old and three-way weaned were randomly allotted to four equal groups [CON (basal diet) group, enterotoxigenic Escherichia coli (ETEC) group, COS group, and COS*ETEC group]. The results showed that COS partially reversed the negative changes in the average daily gain and average daily feed intake caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 59 publications
(93 reference statements)
3
11
0
Order By: Relevance
“…In the present study, the VH and HDR were decreased, but the CD was increased in STEC-challenged pigs. These results are consistent with previous studies showing that pigs challenged with E. coli had a lower VH and HDR in the small intestine [ 29 , 33 , 34 , 35 ]. The E. coli challenge could cause a defect of the intestinal barrier integrity by downregulating the expression of tight junction (TJ) proteins.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the VH and HDR were decreased, but the CD was increased in STEC-challenged pigs. These results are consistent with previous studies showing that pigs challenged with E. coli had a lower VH and HDR in the small intestine [ 29 , 33 , 34 , 35 ]. The E. coli challenge could cause a defect of the intestinal barrier integrity by downregulating the expression of tight junction (TJ) proteins.…”
Section: Discussionsupporting
confidence: 93%
“…According to Liu et al [ 31 ], E. coli can cause inflammation in weaned piglets by boosting WBC counts and neutrophils. A previous study showed that Chito-oligosaccharides with a function similar to XOS can mitigated the increase in the value of neutrophils [ 33 ]. In the current study, during E. coli infection, pigs supplemented with STB had a lower neutrophils-to-lymphocytes ratio than non-supplemented with the STB groups, indicating that inflammation was decreased in piglets with STB supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, following the ETEC F18 challenge, the microbiota configuration of pigs in the GA and GB groups differed from the PC pigs consistently. Similar effects have been observed 40 days postweaning in pigs supplemented with pharmacological levels of zinc oxide during the nursery period ( 72 ), and 21 days postweaning following chito-oligosaccharide supplementation to piglets during an ETEC challenge ( 73 ). We only followed the pigs up to 3 weeks after weaning, but considering the aforementioned studies, a lasting effect of GA and GB supplementation on the microbiota structure of pigs may be expected.…”
Section: Discussionsupporting
confidence: 60%
“…At this point it is not clear if it acts directly on the immune cells or if changes are induced through microbiome alterations. Previous work had shown dietary fiber increases intestinal Foxp3 expression and Tregs cells [ 79 , 80 ]. Feeding long chain inulin-type fructans to NOD/LtJ mice elevated colonic Tregs cells and levels of IL-10 production [ 80 ].…”
Section: Discussionmentioning
confidence: 99%